The school day in Primary - Galván Palomo, Francisco (Avances en Supervisión Educativa, 2013)
We analyze in this article the primary school day, in its dual role as split shift full school day or straight through school day or morning shift. A brief overview of the status us of the topic is done, and a number of issues for discussion are risen. Ending with a suggestion on the task of the Inspectorate of Education in relation to the procedure for determining the type of school day by the educational community.